Prospects for Using Minimum and Zero Tillage in Tropical Lowland Rice - De Datta, S.K.; BOLTONAND, F.R.; LIN, W.L. (Wiley, 1979)
:Four field experiments were conducted at The International Rice Research Institute during the 1975 and 1976 crop seasons to develop minimum and zero tillage techniques for transplanted rice (Oryza sativa L.). High rates of glyphosate followed by a lower rate of paraquat effectively controlled Paspalum distichum L., but not Fimbristylis littoralis L. The tenminimum tillage treatments based on different combinations and sequences of pre‐plant herbicide application, tillage and flooding, gave a similar grain yield to conventional tillage, and significantly higher grain yield than zero tillage treatments. Conventional, minimum and zero tillage were compared over four successive crops. After two crops with zero tillage, the plots were dominated by the perennials, P. distichum and Scirpus maritimus L., but with minimum or conventional tillage, weed control and grain yield were satisfactory. Efficiency of nitrogen fertilizer usage by the crop was the same with minimum as with conventional tillage but higher than with zero tillage and was increased by placement at 10 cm depth. The studies indicate that minimum tillage systems are a dependable alternative to conventional tillage for lowland rice production.